Development of Problem-Based Tools to Improve Thinking Abilities in In-Service PPG Program Students - Rengkuan, Mariana; Sompotan, Armstrong F.; Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2024)
This research aims to develop problem-based learning tools that empower students' thinking abilities in the In-service Teacher Professional Education Program at Unima. The learning tools developed consist of modules and LKPD for the Biology Learning Tool Development course. The development model used is the ADDIE development model consisting of four stages, namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The results of the research are the feasibility of the learning tools which are seen based on the aspects of validity, practicality, and effectiveness of the learning tools. Next, to see the effectiveness of problem-based learning tools on thinking ability using One Group Pretest-Posttest Design which was implemented on 29 PPG Daljab Category 1 students, class 3 of 2023. The results of the research show that the learning tools are very valid with an assessment score interval between 3.5-4 and reliability between 95%-98%. The learning implementation is categorized as very good with an assessment score interval between 3.6-4 with an average reliability of 97%, the average readability level of the device based on the Gunning Fox index is 11 with medium criteria, the readability percentage of the learning device based on the readability sheet of the learning device is 97% and students provide a positive response to learning tools was 98%. The increase in students' cognitive learning outcomes can be seen from the average N-gain value for all students, namely 0.68 with medium criteria, classical completeness of 100%, and indicator completeness with an interval of 2.5-3.5. Based on the results of this research, it can be concluded that problem-based learning tools in the biology teaching tool development course are suitable for use to improve the thinking skills of students in the PPG Daljab Program at Unima.